2013
DOI: 10.5040/9781492595502
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Psychology

Abstract: Exercise Psychology, Second Edition, addresses the psychological and biological consequences of exercise and physical activity and their subsequent effects on mood and mental health. Like the first edition, the text includes the latest scholarship by leading experts in the field of exercise adoption and adherence. This edition also incorporates research on lifestyle physical activity to reflect this growing area of study over recent years. In contrast to other exercise psychology textbooks grounded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
22

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(154 citation statements)
references
References 0 publications
4
128
0
22
Order By: Relevance
“…This search for "outer recognition" has been associated with controlled motivation, which in turn leads to negative outcomes (Ingledew & Markland, 2008). Indeed, gym exercisers with a stronger intrinsic motivation have been shown to commit themselves in exercise for longer periods and report higher levels of intention and adherence to exercise (Buckworth, Dishman, O'Connor & Tomporowski, 2013). In contrast, participants engaging in physical exercise for external reasons and motivations are more prone to experience a weakening of their intention towards exercising, ultimately leading to withdrawal (Rodrigues et al, 2018).…”
Section: Multi-group Analysismentioning
confidence: 99%
“…This search for "outer recognition" has been associated with controlled motivation, which in turn leads to negative outcomes (Ingledew & Markland, 2008). Indeed, gym exercisers with a stronger intrinsic motivation have been shown to commit themselves in exercise for longer periods and report higher levels of intention and adherence to exercise (Buckworth, Dishman, O'Connor & Tomporowski, 2013). In contrast, participants engaging in physical exercise for external reasons and motivations are more prone to experience a weakening of their intention towards exercising, ultimately leading to withdrawal (Rodrigues et al, 2018).…”
Section: Multi-group Analysismentioning
confidence: 99%
“…Possible explanations for the antidepressant effect associated with activity include immediate‐to‐short‐term and longer‐term physiological mechanisms (e.g. increased synthesis of norepinephrine and serotonin, increased blood circulation, Buckworth, Dishman, O'Connor, & Tomporowski, ; increased synthesis of endorphins, dopamine, and endocannabinoids, Ekkekakis, ; neuroimmune modulation, i.e. reduced inflammation and oxidation stress, Eyre & Baune, ; enhanced energy and lower fatigue, Loy, O'Connor, & Dishman, ; circadian rhythm reset through natural light exposure, Stephenson, Schroder, Bertschy, & Bourgin, ) as well as psychological mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The positive psychological benefits of exercise are well documented, including reduction of depression, alleviating psychological distress, and improvement in various measures of well-being (e.g., Crone et al, 2005;2006;Dunn & Jewell, 2010). Cross-sectional epidemiological studies have indicated significantly fewer depressive and anxious symptoms amongst physically active persons (Buckworth & Dishman, 2002) and there have been positive findings suggesting exercise could be a beneficial strategy to improve psychological well-being in mothers (see Daley et al (2007;2009) and Davis and Dimidjian (2012) for reviews). However, the relationship of exercise with mothers' psychological well-being has not been assessed utilizing large-scale samples specifically addressing this issue in Australian/New Zealand populations.…”
Section: Introductionmentioning
confidence: 99%